The Thyroid Gland: A Crossroad in Inflammation-Induced Carcinoma? An Ongoing Debate with New Therapeutic Potential. - Bozec, A.; Lassalle, S.; Hofman, V.; Ilie, M.; Santini, J.; Hofman, P. (Current Medicinal Chemistry, 2010)
Chronic infection and inflammation contribute to around 25% of cancer cases worldwide. While a direct link between several types of human malignancies and inflammation has now been established, in particular at the gastrointestinal level, the relationship between inflammation and thyroid cancer and the pathophysiology of chronic inflammation that induces papillary thyroid carcinoma (PTC) are still subjects of debate. However, several epidemiological and morphological studies have strongly suggested an increased risk of PTC in patients with Hashimoto's thyroiditis (HT). As in HT, an intense immune infiltrate is associated with certain PTC and might play a critical role in the regulation of carcinogenesis and in carcinoma progression. Proinflammatory molecules, such as cytokines and chemokines, which are produced by immune infiltrate in the tumor microenvironment, contribute to the regulation of key cellular processes for cancer onset and progression, in particular for tumor cell proliferation, apoptosis, autophagy, angiogenesis and metastasis. Molecular studies have identified activation of the RET/PTC rearrangement&ndashinduced MAPK signaling pathway as the driving force in the development of PTC in the context of HT. These genetic alterations may be favored by chronic inflammation. In this regard, the RET oncoprotein and its downstream effectors, such as those implicated in the activation of the MAPK pathway, as well as inflammatory molecules of the tumor microenvironment could be promising molecular targets for new therapeutic strategies for thyroid cancer. This review focuses on the complex link between thyroid cancer and chronic inflammation and highlights the different current hypotheses regarding the role of the immune cell microenvironment in the initiation and progression of PTC.
Keywords: apoptosis